Enhancing Student Learning Motivation Through the Implementation of Project-Based Learning (PJBL) with Interactive Digital Books - Prayuda, Meikardo Samuel; Lumbangaol, Reni Rosianna; Hutabarat, Renato Gema Nugraha; Tanjung, Darinda Sofia (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
The study presents the use of interactive digital books that are focused on project-based learning to boost the motivation of students to learn. One of the required subjects for students enrolled in the English education study program at the Catholic University of Saint Thomas Medan is teaching English as a foreign language. The following issues were discovered during observations conducted in the class of 2020 students enrolled in the English Education Study Program at the Catholic University of Saint Thomas Medan. Students are completing courses on teaching English as a foreign language. Low student motivation for learning is demonstrated by the student's inability to comprehend the lecturer's explanations of the material. Their laziness comes from studying and reluctance to read the material they have acquired. And their boredom comes from listening to the lecturer explain the material. Using digital books is one strategy professors can employ to boost student motivation for learning. Students are required to have the motivation or drive to complete learning activities in higher education in order to meet their desired learning objectives, thanks to the digital book. Descriptive qualitative research is what this study was. A questionnaire was used as the data collection method, and 32 students responded to it. The usage of interactive digital books based on Project Based Learning (PjBL) has been shown to boost student learning motivation, according to the study's findings. 96.37% of the results are extremely high.